Lithium–Lanthanide Bimetallic Metal–Organic Frameworks towards Negative Electrode Materials for Lithium‐Ion Batteries. Issue 25 (20th April 2020) - Song, Xiao‐Yi; Zhang, Yu‐Hang; Sun, Ping‐Ping; Gao, Jun; Shi, Fa‐Nian
Abstract: Novel lithium–lanthanide (Ln: cerium and praseodymium) bimetallic coordination polymers with formulas C10 H2 LnLiO8 (Ln: Ce (CeLipma) and Pr (PrLipma)) and C10 H3 CeO8 (Cepma) were prepared through a simple hydrothermal method. The three compounds were characterized by means of FTIR spectroscopy, X‐ray diffraction, single‐crystal X‐ray diffraction, SEM, TEM, and X‐ray photoelectron spectroscopy. The results of structural refinement show that they belong to triclinic symmetry and P 1 ‾ space group with cerium (or praseodymium) and lithium cations, forming coordination bonds to oxygen atoms from different pyromellitic acid molecules, and leading to the construction of 3D structures. It is interesting to note that the frameworks exclude any coordination water and lattice water. As an electrode material for lithium‐ion batteries, CeLipma exhibits a maximum capacity of 800.5 mAh g −1 and a retention of 91.4 % after 50 cycles at a current density of 100 mA g −1 . The favorable electrochemical properties of the lanthanide coordination polymers show potential application prospects in the field of electrode materials. Abstract : Expanded capacity : Three Ln−Li metal–organic frameworks (MOFs; Ln=Ce and Pr) were successfully designed and structurally characterized. The unique electrochemical performances of Ln−Li MOFs lead to promising applications as next‐generation electrode materials for lithium‐ion batteries.